Studi Eksegesis mengenai Kerajaan Mesias Menurut Yesaya 2:1-4 - Farel Yosua Sualang (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2020)
The main problem regarding the meaning of the Hebrew word "haggôyîm" in Isaiah 2: 1-4, which is interpreted as "the nations" gives a different interpretation. The analysis of "the Messiah's reign according to Isaiah 2: 1-4" is worth studying in regard to its use described in the old and new covenants as a research objective in this article. Hermeneutic prophetic approach, which consists of several procedures to explain the subject under study. The type of prophetic literature in Isaiah 2: 1-4 has the structure in the form of the prophecy of salvation as a methodology for interpreting this text. The presentation in Isaiah 2: 1-4 wants to show a revelation of the Government led by the Messiah related to His coming, His Government, Citizens of His Kingdom and His coming. This can be demonstrated by the expression of the coming of the Messiah, explanation of the central government of Messiah, the citizens of the Messiah's kingdom, the effects of Messiah's reign, the full knowledge of God and the sins of the nations being judged, where he will judge the world from His throne in the Temple.Masalah utama mengenai maksud kata Ibrani “haggôyîm” dalam Yesaya 2:1-4 yang diartikan sebagai “bangsa-bangsa” memberikan suatu interpretasi yang berbeda-beda. Analisis mengenai “Pemerintahan Mesias menurut Yesaya 2:1-4” patut untuk dikaji dalam memerhatikan penggunaannya yang dijelaskan pada perjanjian lama dan perjanjian baru sebagai suatu tujuan penelitian dalam artikel ini. Pendekatan hermeneutika nubuatan, yang terdiri dari beberapa prosedur ataupun metode-metode yang dipakai untuk menjelaskan subjek yang diteliti. Jenis sastra nubuatan dalam Yesaya 2:1-4 memiliki struktur yang berbentuk nubuatan keselamatan sebagai metodologi dalam menafsirkan teks. Pemaparan dalam Yesaya 2:1-4 ingin menunjukkan suatu penyataan tentang Pemerintahan yang dipimpin oleh Sang Mesias yang terkait dengan kedatanganNya, PemerintahanNya, Warga KerajaanNya, pengenalan yang penuh akan Allah dan kedatanganNya. Hal ini dapat ditunjukan dengan ekspresi kedatangan Mesias, penjelasan tentang pusat pemerintahan Mesias, warga kerajaan Mesias (orang-orang Israel yang sudah diselamatkan), dampak-dampak pemerintahan Mesias, pengenalan penuh akan Allah dan dosa bangsa-bangsa dihakimi, dimana Ia akan menghakimi dunia dari tahta-Nya di Bait Allah.